Efek Sinergitas Ekstrak Kulit Jeruk (Citrus sinensis L) Pada Patch Bioselulosa Dalam Meningkatkan Penyembuhan Luka Bakar: Synergetic Effect of Orange Peel Extract in Biocellulose Patch Toward Burn Wound Healing - Roska, Tri Puspita; Sahati, Syahidah; Fitrah, Andi Dinul; Juniarti, Nana; Djide, Natsir (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2018)
Burns is one of the incidents that can lead to death (mortality). One of the natural products that have potential to serve as an alternative treatment of burns is orange peel. Orange peel has a chemical composition such as ascorbic acid, vitamin E, vitamin A, and polyphenols as antioxidants that inhibit free radicals responsible in the pathogenesis of both acute and chronic inflammatory. In this study, formulation was made in the form of biocellulose which is the primary metabolism product of bacteria. The purpose of this research was to obtain the concentration of the extract of orange peel on bioselullose that have the effect of decreasing the burn wound in rats. Orange peel was extracted then fortified into biocellulose with a concentration of 3%, 6%, and 9%. After that, the wound healing was tested on animals in the form of decreasing the wound diameter. The results showed that the concentration of extract of orange peel 3% on the fortification of biocellulose showed the good percentage of burn wound decreasing i.e. 45.52% with diameter average of 18.35 mm. This result indicates the concentration of extract of orange peel 3% is better than others.